'Discrimination Preferred': How Ordinary Verbal Bigotry Harms. Issue 2 (3rd April 2021) - Caponetto, Laura; Cepollaro, Bianca
ABSTRACT: A widespread thesis in contemporary philosophy of language is that certain speech constitutes, rather than merely causes, harm. McGowan develops a prescriptive account of harm constitution, according to which harm-constituting speech enacts norms that prescribe harm. Ordinary verbal bigotry, she claims, is harmful in this sense. We submit that the norms enacted by ordinary racist (or otherwise bigoted) utterances are not prescriptive. In our view, ordinary verbal bigotry enacts 'non-neutrally' permissive norms rendering harmful behaviours locally permitted—and indeed preferred over non-harmful options. We conclude by arguing that, although ordinary verbal bigotry enacts non-prescriptive norms, it can still constitute harm.